Bold love - Allender, Dan B.; Wounded Heart Ministries; Longman, Tremper, III, 1952- (Colorado Springs, CO Navpress, 1992)
Includes bibliographical references.
Keywords: Love -- religious aspects -- Christianity; Love-hate relationships -- religious aspects -- Christianity; Reconciliation -- religious aspects -- Christianity